Echocardiographic Structure and Function in Hypertensive Disorders of Pregnancy: A Systematic Review. (September 2016) - Castleman, James S.; Ganapathy, Ramesh; Taki, Fatima; Lip, Gregory Y.H.; Steeds, Richard P.; Kotecha, Dipak
Abstract : Background—: Echocardiography is commonly used to direct the management of hypertensive disorders in medical patients, but its application in pregnancy is unclear. Our objective was to define the use of echocardiography in pregnancies complicated by gestational hypertension (GH) and preeclampsia. Methods and Results—: We performed a systematic review of articles using an electronic search of databases from inception to March 2015, prospectively registered with PROSPERO (CRD42015015700). Eligible studies included pregnant women with GH or preeclampsia, evaluating left ventricular structure and function using echocardiography. The search strategy identified 36 studies, including 745 women with GH and 815 women with preeclampsia. The populations were heterogeneous with respect to clinical characteristics, parity, and risk of bias. Increased vascular resistance and left ventricular mass were the most consistent findings in GH and preeclampsia. Differentiating features from normal pregnancy were left ventricular wall thickness of ≥1.0 cm, exaggerated reduction in E/A, and lateral e′ of <14 cm/s. There was disagreement between studies with regard to cardiac output because of the timing of echocardiography, although reduced stroke volume was an indicator of adverse prognosis. Diastolic dysfunction and left ventricular remodeling are most marked in severe and early-onset preeclampsia, but are also markers of preeclampsia before clinical manifestation, and are associated with adverse outcomes. Conclusions—: Echocardiography is a valuable tool to stratify risk and can guide management and counseling in the preclinical and clinical phases of GH and preeclampsia. Changes in cardiac function and morphology are recognizable at an asymptomatic early stage and correlate with disease severity and adverse outcomes. Abstract : Supplemental Digital Content is available in the text.